Synthesis, Characterization, and Evaluation of MCF-7 (Breast Cancer) for Schiff, Mannich Bases, and Their Complexes - Ali Abdulkareem Al-Khazraji (Indonesian Journal of Chemistry, 2024)
A new synthesis of Schiff (K) 6 and Mannich bases (Q) 7 had formed compound (Q) 7 by reacting compound (K) with N-methylaniline at the presence of formalin 35% to given Mannich base (Q). Additionally, new complexes were formed by reacting Schiff base (K) with metal salts CuCl2·2H2O, PdCl2·2H2O, and PtCl6·6H2O by 2:1 of M:L ratio. New ligands and their complexes were characterized, exanimated, and confirmed through several techniques, including FTIR, UV-visible, 1H-NMR, 13C-NMR spectroscopy, CHN analysis, FAA, TG, molar conductivity, and magnetic susceptibility. These compounds and their complexes were screened against breast cancer cells. It was determined that several of these compounds had a significant anti-breast cancer effect due to their ability to induce cell death and reduce tumor growth. Metal complexes have been thoroughly studied as a potential anti-cancer therapy and have shown promising results. It was revealed these complexes uniquely affect the biological processes involved in cancer growth, leading to apoptosis and fading of cells. To form MCF-7 cell cultures, MCF-7 cells were seeded in 96-well plates at an appropriate density (5 × 105 cells/well). Metal complexes utilized in MCF-7 therapy have the potential to disband some of the harms associated with chemotherapy, such as drug resistance and toxicity.